Dynamic changes of gut and lung microorganisms during chronic obstructive pulmonary disease exacerbations - Zhe Sun; Qiu‐Li Zhu; Yun Shen; Tao Yan; Xin Zhou (Kaohsiung Journal of Medical Sciences)
Abstract Increasing evidence has indicated the intimate relationship between the gastrointestinal tract and respiratory tract. The microbial ecosystem has been confirmed to share key conceptual features with gut‐lung microbiome disorder and dysregulation during chronic obstructive pulmonary disease (COPD) exacerbations. However, the dynamic changes of the gut‐lung microbiome during COPD exacerbations and its potential role in disease etiology remain poorly understood. The present study investigated the dynamic changes of gut and lung microorganisms during acute exacerbation of chronic obstructive pulmonary disease (AECOPD). A longitudinal 16S ribosomal DNA survey of the gut and lung microbiome was completed on 90 feces and sputum samples collected from 15 subjects with AECOPD at three visits, which were defined as exacerbation, seven‐day stable state. The present analysis revealed a dynamic gut‐lung microbiota, where changes appeared to be associated with exacerbation events indicative of specific exacerbation phenotypes. Antibiotic and steroid treatments appeared to have differential effects on the gut‐lung microbiome, and the microbiome was associated with disease progression, but not with severity. The abundance and diversity of the microbiome was strongly influenced by the disease progression and therapy. Using culture‐independent methods to impact the gut and lung microbiota on AECOPD may be the key to understanding the interactions between the gut and lung, highlighting its potential as a biomarker, and possibly a target for future respiratory therapeutics.